PERLINDUNGAN HUKUM HAK CIPTA GAME LUAR NEGERI DI INDONESIA BERDASARKAN UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA - NIM. A1011181161, AUFA DZULFAR RINALLDY (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract In this era of very advanced technological development, application developers or Developers create entertainment applications in the form of online games that can be played on various online media such as smartphones and personal computers. This video game can be easily accessed by the public. This study discusses the Legal Protection of Copyright for Foreign Games in Indonesia Based on Law Number 28 of 2014 Concerning Copyright. Then it will also discuss how the procedures that can be carried out by the Creator holding the Copyright of foreign Games will register their Copyright in Indonesia. It will also discuss the rights obtained by the Creator or Copyright holder of foreign games who register their Copyright in Indonesia, in the form of Exclusive Rights which include Moral Rights and Economic Rights. It will also discuss how long the Copyright protection period is valid and legal protection against violations that may occur against the Copyright. By using normative legal research methods (legislative approach) conducted by reviewing various data sources related to the research problem. The primary legal material used in this study is Law Number 28 of 2014 concerning Copyright. There are also secondary legal materials that provide explanations to primary legal materials, such as the TRIPS (Agreement on Trade-Related Aspects of Intellectual Property Rights) agreement, the Directorate General of Intellectual Property (DJKI) Module, law books, research journals and expert opinions. By using normative legal research methods (legislative approach) conducted by reviewing various data sources related to the research problem. The primary legal material used in this study is Law Number 28 of 2014 concerning Copyright. There are also secondary legal materials that provide explanations to primary legal materials, such as the TRIPS (Agreement on Trade-Related Aspects of Intellectual Property Rights) agreement, the Directorate General of Intellectual Property (DJKI) Module, law books, research journals and expert opinions. So it can be found that the procedure for recording Copyright carried out by the Creator or Copyright holder of foreign games is carried out through an Intellectual Property consultant based on Article 67 Paragraph (3) of Law Number 28 of 2014 concerning Copyright. This recording is carried out with the aim of ensuring the protection of Exclusive Rights obtained by the Creator or Copyright holder of foreign games in the form of Moral Rights and Economic Rights. The legal protection obtained by the Creator or Copyright holder is in the form of legal protection that applies for a period of 50 years against the Copyright of games which in this case are included in the Copyright of video games for possible Copyright violations. Keywords: Copyright Registration, Copyright of Foreign Games in Indonesia, Copyright Registration of Foreign Games in Indonesia, Legal Protection of Game Copyright. Abstrak Di zaman perkembangan teknologi yang sangat maju ini, para pengembang aplikasi atau Developer menciptakan aplikasi hiburan berupa game online yang bisa dimainkan di berbagai sarana online seperti smartphone dan personal computer. Video game ini dapat diakses dengan mudah oleh masyarakat. Penelitian ini membahas mengenai Perlindungan Hukum Hak Cipta Game Luar Negeri Di Indonesia Berdasarkan Undang-Undang Nomor 28 Tahun 2014 Tentang Hak Cipta. Kemudian akan dibahas juga tentang bagaimana prosedur yang dapat dilakukan oleh Pencipta pemegang Hak Cipta dari Game luar negeri akan mencatatkan Hak Ciptanya di Indoneisa. Akan dibahas juga hak-hak yang didapat oleh Pencipta atau pemegang Hak Cipta game luar negeri yang mencatatkan Hak Ciptanya di Indonesia, berupa Hak Eksklusif yang meliputi Hak Moral dan Hak Ekonomi. Akan dibahas juga berapa lama jangka waktu perlindungan Hak Cipta berlaku dan perlindungan hukum terhadap pelanggaran yang mungkin akan terjadi terhadap Hak Cipta tersebut. Dengan menggunakan metode penelitian hukum normatif (pendekatan perundang-undangan) yang dilakukan dengan menelaah berbagai sumber data yang berkaitan dengan masalah penelitian. Bahan hukum primer yang digunakan dalam penelitian ini dalah Undang-Undang Nomor 28 Tahun 2014 Tentang Hak Cipta. Terdapat juga bahan hukum sekunder yang memberikan penjelasan terhadap bahan hukum primer, seperti perjanjian TRIPS (Agreement on Trade-Related Aspects of Intellectual Property Rights), Modul Direktorat Jenderal Kekayaan Intelektual (DJKI), buku hukum, jurnal penelitian dan pendapat para ahli. Sehingga dapat ditemukan hasil bahwa prosedur pencatatan Hak Cipta yang dilakukan oleh Pencipta atau pemegang Hak Cipta game luar negeri dilakukan melalui konsultan Kekayaan Intelektual berdasarkan Pasal 67 Ayat (3) Undang-Undang Nomor 28 Tahun 2014 Tentang Hak Cipta. Pencatatan ini dilakukan dengan tujuan untuk memastikan perlindungan Hak Eksklusif yang didapat oleh Pencipta atau pemegang Hak Cipta game luar negeri berupa Hak Moral dan Hak Ekonomi. Perlindugan hukum yang didapatkan oleh Pencipta atau pemegang Hak Cipta berupa perlindungan hukum yang berlaku dalam jangka waktu 50 tahun terhadap Hak Cipta game yang dalam hal ini termasuk ke dalam Hak Cipta permainan video atas pelanggaran Hak Cipta yang mungkin saja terjadi. Kata kunci: Pencatatan Hak Cipta, Hak Cipta Game luar negeri di Indonesia, Pencatatan Hak Cipta Game luar negeri di Indonesia, Perlindungan Hukum terhadap Hak Cipta game.